Getting Rid of Intracellular Aβ - Loss of Cellular Degradation Leads to Transfer Between Connected Neurons - Agholme, Lotta; Hallbeck, Martin (Current Pharmaceutical Design, 2014)
The sporadic, late onset form of Alzheimer's disease (AD) shares pathological hallmarks with the familial form; however, no clear reason for increased β-amyloid (Aβ) generation has been found in the former. It has long been speculated that the late onset form of AD is caused by reduced degradation and/or clearance of Aβ. Indeed, both intracellular degradation systems, the proteasomal and lysosomal systems, have been shown to be defective in AD. Reduced proteasome activity increases levels of intracellular and secreted Aβ. Furthermore, accumulation of improperly degraded Aβ in the lysosomes causes lysosomal disruption and cell death. We recently showed that oligomeric Aβ can be transmitted from one neuron to another, which causes neurotoxicity. In both the donating and receiving cells, Aβ accumulates in the endo-lysosomal compartment. It is possible that ineffective degradation of Aβ causes its transfer to neighboring neurons, thereby spreading AD pathology. This review summarizes the data underlying the idea of reduced Aβ clearance and subsequent Aβ spread in AD, and also suggests new therapeutic methods, which are aimed at targeting the degradation systems and synaptic transfer. By enhancing degradation of intracellular accumulated Aβ, it can be possible to remove it and avoid Aβ-induced neurodegeneration without disturbing the endogenously important pool of secreted Aβ. Additionally, drugs targeted to inhibit the spread of intracellular toxic Aβ aggregates may also be useful in stopping the progression of pathology, without affecting the level of Aβ that normally occurs in the brain.
Keywords: Alzheimer' s disease